PENGARUH PENGALAMAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DENGAN LINGKUNGAN KERJA FISIK SEBAGAI VARIABEL MODERASI PADA PT. CITRA RIAU SARANA KECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI - , Kurniawaty Fitri, Hendra Saputra , Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of working experience and working discipline on employee performance with the physique working environment as a moderating variable at PT.citra riau sarana logas tanah darat subdistrict kuantan singingi regency. Population in this study include permanent employees of PT,citra riau sarana t0 81 people. Primary data was collected by using a questionnaire as an instrument to prove the result of the study, to test the hypothesis in this study, using multiple regression using spss software version for windows. Sampling using non probability sampling method with saturated sampling technique. The results of the study show that: 1)there is a significant influence between work experience on the performance of employee of PT.citra riau sarana. 2) there is a significant influence between the influence of discipline on the performance of employee of PT.citra riau sarana. 3) there is a significant influence between work experience on employee performance and the work environment as a moderating variable at  PT.citra riau sarana. 4) there is a significant influence of work discipline on employee performance with the work environment as a moderating variable at  PT.citra riau sarana. Keywords : experience, discipline, environment, performance